The Innovative Health Initiative public–private partnership: a catalyst for big data-driven health research and innovation - Vaudano, Elisabetta (Frontiers in Medicine, 2025)
The use of “Big Data” in health research could be a game changer to revolutionize the field and drive innovation. However, the complexity of health data and of the healthcare ecosystem makes big data applications challenging. To overcome these challenges, it is essential that all stakeholders, both data owners and users, feel comfortable with the data use and the results of the analyses. This can only be achieved using a collaborative approach that prioritizes transparency and trust. The European Innovative Health Initiative (IHI) is a prime example of a successful public–private partnership that has achieved this. By fostering a culture of collaboration and trust, the IHI has enabled unprecedented access to large amounts of health data, improved data quality and standards, and created valuable resources and knowledge for progress in areas of unmet public health need. This perspective explores the IHI model and highlights examples from its projects that demonstrate its power as a catalyst for big data-driven health research and innovation. By sharing lessons learned and best practices, we aim to contribute to the development of a robust data-driven evidence base for the translation of research into improved patient care practices and products.